Exploratory research on the impact of Mysejahtera application on to the elderly based on user experience / Nur Aisya Roslan and Saiful Bahar Salim - Roslan, Nur Aisya; Salim, Saiful Bahar (UiTM Press, 2024)
The number of smartphone users in Malaysia is predicted to rise by 1.74 million by 2025, owing to the country’s expanding population. According to Statista (2021), in a survey on smartphone ownership, only 30% of respondents aged 65 and up have a smartphone. However, the researcher shall overview an increasing number of elderly individuals interacting with digital technology during the Covid-19 pandemic. The problem statement has been found in other scholars stating that most people over the age of 60 use mobile phones for minimal purposes, such as calling or SMS in emergencies (Coates. H, 2001). Most complaints are related to displays that are too small and difficult to see, buttons and characters being too small, causing them to push wrong numbers frequently (Hassan. H et al., 2014). Based on previous literature, the problems faced by the elderly using mobile phones are form factors and user interface (UI.) of mobile phone devices such as rubbery buttons, small screen display, small buttons, colors, backlighting, and text characters for viewing (Md Nasir et al.,2008). In this research, the researcher will conduct an exploratory study on the impact of the MySejahtera Application on the elderly. As we know, the elderly have severe difficulty with sight vision and other effects. Thus, the interface design and navigability with the information presented on the screen, and the number of functions, are amongst factors that make smartphone adoption difficult for the elderly. On the other hand, this research aims to determine or discuss UI/UX recommendations focused on elderly users. The outcome of this research will benefit the elderly in Malaysia as a developing country in terms of technological utilization.